Understanding the Psychological Processes of the Racial Match Effect in Asian Americans - Meyer, Oanh (2011)
Some studies on mental health outcomes research have found that when clients and therapists are ethnically or racially matched, this tends to be related to greater satisfaction and better outcomes. However, the precise underlying mechanism for the match effect has not been extensively examined. In this experimental study, we tested the effect of racial match on critical counseling processes (i.e., therapist credibility and the working alliance) using a sample of 171 Asian American respondents. We also examined Asian ethnic identification as a potential moderator of the racial match effect. Structural equation modeling analyses indicated that racially matched individuals perceived greater experiential similarity with the therapist than nonmatched individuals, and experiential similarity was positively associated with therapist credibility. Although racial match did not predict attitudinal similarity, attitudinal similarity was strongly related to the working alliance and therapist credibility. Counseling implications are discussed.